2018
DOI: 10.1210/js.2018-00010
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 23–Induced Hypophosphatemia in Acute Leukemia

Abstract: Fibroblast growth factor 23 (FGF23)–induced hypophosphatemia is a rare paraneoplastic syndrome of phosphate wasting that, if unrecognized, may cause tumor-induced osteomalacia. It is classically associated with benign mesenchymal tumors but occasionally has been found in patients with other malignancies. Hypophosphatemia has been associated with acute leukemia but has not previously been reported to be due to inappropriate FGF23 secretion. Here, we describe FGF23-induced severe hypophosphatemia and renal phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…PMTs are usually small, benign and characterised by low grade and mitotic index, requiring PET imaging to be detected [3]. However, it has also been linked with malignant haematological and solid tumours such as leukaemia [14], head and neck cancer [15], B cell non-Hodgkin's lymphoma [16], sarcoma [17], anaplastic thyroid carcinoma [18], small cell lung cancer [19], prostate cancer [20] and adenocarcinoma of the colon [21].…”
Section: Discussionmentioning
confidence: 99%
“…PMTs are usually small, benign and characterised by low grade and mitotic index, requiring PET imaging to be detected [3]. However, it has also been linked with malignant haematological and solid tumours such as leukaemia [14], head and neck cancer [15], B cell non-Hodgkin's lymphoma [16], sarcoma [17], anaplastic thyroid carcinoma [18], small cell lung cancer [19], prostate cancer [20] and adenocarcinoma of the colon [21].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the mouse study, cFGF-23 rather than iFGF-23 may be critical for the interactions with RBC. Comparable increases of cFGF-23 levels were also found in acute myeloid leukemia (46) and in patients with chronic kidney disease and renal anemia (47), which in the latter also correlated negatively with hemoglobin values. Importantly, we collected a unique set of bone biopsies from MDS patients.…”
Section: Discussionmentioning
confidence: 79%
“…This case is the first report of a ZBTB20-JAK2 fusion defining a case of MLN-EGR presenting as B-ALL. Although remission following treatment of MLN-PJ with JAK2 inhibitors has been reported (Lierman et al 2012;Rumi et al 2013Rumi et al , 2015Bain and Ahmad 2014;Schwaab et al 2015;Reiter and Gotlib 2017), there is a near-complete absence of reported responses to these therapies targeting JAK mutations and/or fusion genes in B-ALLs, including Ph-like ALLs (Roberts et al 2014;Reinert et al 2018). This patient's case was appropriately initially classified as a B-ALL, and therapy was selected based on this diagnosis.…”
Section: Discussionmentioning
confidence: 98%